Aleppo: Arabic Music or Chinese Orchestral Work? - Heng, Lena (Circuit, 2025)
Aleppo is a concerto for the sanxian and Chinese orchestra, by Singaporean composer Wang Chenwei. The work uses Chinese instruments but is written with modes and metrical concepts borrowed from Arabic music and programmatic content based on Aleppo and the Syrian war. While the timbre of the instruments is distinctly Chinese, the composer combines these instruments masterfully and draws on various orchestration techniques to create sounds that evoke the Middle East and the Arabic world such that one almost forgets that none of the instruments are actually Arabic instruments. In a close reading of this piece, combined with spectral analyses of a recording, I endeavour to illustrate how the composer creates the illusion of Arabic music through skillful selection and masterful orchestration techniques.